2013
DOI: 10.1007/s00330-013-2874-2
|View full text |Cite
|
Sign up to set email alerts
|

Thickening of the inferior glenohumeral capsule: an ultrasound sign for shoulder capsular contracture

Abstract: • Ultrasound is increasingly used to diagnose shoulder problems. • The thickness of the inferior glenohumeral ligament is measurable in the axilla. • The inferior glenohumeral ligament appears thickened in shoulders with capsular contracture. • Capsular contracture ultrasound features can be associated with other rotator cuff problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 23 publications
2
82
0
1
Order By: Relevance
“…Homsi et al 8 concluded that US was access to determine CHL thickness and the average thickness is significantly greater in adhesive capsulitis shoulders (3 mm) than in painful shoulders (1.39 mm) and asymptomatic shoulders (1.34 mm). Michelin et al 7 also used US to measure the inferior glenohumeral capsule thickness with a transducer placed within the axilla in maximally abducted shoulders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Homsi et al 8 concluded that US was access to determine CHL thickness and the average thickness is significantly greater in adhesive capsulitis shoulders (3 mm) than in painful shoulders (1.39 mm) and asymptomatic shoulders (1.34 mm). Michelin et al 7 also used US to measure the inferior glenohumeral capsule thickness with a transducer placed within the axilla in maximally abducted shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…US and US-arthrography images were analyzed in consensus by two radiologists (G.X.Y and L.M), who were blinded to patients' demographic date, history, group, and MR findings. For US evaluation, thickness of CHL and inferior glenohumeral capsule were obtained, rotator interval abnormality and biceps sheath effusion was observed and characterized as present or absent 7,8,18,19 . Rotator interval abnormality was diagnosed with the detecting of hypoechoic echotexture or increased vascular flow in rotator interval.…”
Section: Mri Protocol Mri Was Performed With a 15 T Mr System (Signmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the CHL, rotator interval, and inferior glenohumeral (GH) capsule were scanned in sequence with patients sit in a chair. For assessment of CHL, the transducer was placed on the lateral border of the coracoid process to obtain a longitudinal image and to measure the thickness of the CHL (the thickest portion) with the shoulder in a neutral position and the forearm extended 8 . The rotator interval was scrutinised with the patient’s fist held by the side to detect if there were any increased echotexture or increased vascularity by using grey-scale and color Doppler sonography 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The traditional shoulder arthrography was used to assess the volume of the glenohumeral joint. Both US and MRI have high soft-tissue resolution and are widely used to assess coracohumeral ligament (CHL) and capsule and synovium for AC 810 . Numerous specific MRI/MRA findings have been reported to diagnose AC, which includes thickening of the CHL, thickening of the joint capsule in the rotator cuff interval and axillary recess, effacement of the axillary recess, obliteration of subcoracoid fat triangle and so on 7, 1013 .…”
Section: Introductionmentioning
confidence: 99%